The accuracy of extraoral periapical radiography on determining the working length in endodontic treatment: narrative review - Kusumawati, Khairin Yonni; Yanuaryska, Ryna Dwi; Shantiningsih, Rurie Ratna (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI); Vol 6 No 1 (2022): Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI)DO - 10.32793/jrdi.v6i1.770, 2022)
Objectives: This review article is aimed to determine the accuracy of extraoral periapical radiography as a determinant of the working length in endodontic treatment and the advantages and disadvantages of this technique. Review: Endodontic treatment is a dental treatment for damages reaching the pulp which aims to maintain the tooth. One way to succeed in endodontic treatment is to determine an accurate working length. The working length can be determined by intraoral periapical radiography examination but some people are sensitive to intraoral film placement. The placement of film on periapical radiography extraorally is needed. Conclusion: The study showed that the extraoral periapical radiography had more than 75% accuracy in determining the working length depending on angulation used. This review concludes that extraoral periapical radiography can be used in patients who can not tolerate to intraoral film placement with an accuracy that is not significantly different from that of the intraoral periapical radiography but is not meant to be replaced intraoral periapical radiography.